Yellow corky vein- a viroid disease of citrus in India - RUSTEM, F S; AHLAWAT, Y S (The Indian Journal of Agricultural Sciences, 2013)
Yellow corky vein disease of citrus in India is known to cause yield loss up to 89.7% in kagzi lime in Assam. The disease is widely Â disease is widely distributed in India and is being disseminated inadvertantly through vegetative propagation. Experimentally,the Â disease was transmitted by wedge and bud grafting and infected 19 hosts in Rutaceane family. Kagzi lime [Citrus aurantifolia (Christm).Swing] has been identified as an infecator host of yellow corky vein disease pf citrus. Transmission of the disease was maximum at a temperature of41.7/22.7 (PAGE AND R-PAGE) and nucleases treatment of samples revealed the association of viroid-like ribosenucleic acid in yellow corky vein disease which is a new record.